Diseño y construcción de una bomba de calor asistida por energía solar utilizada para el calentamiento de agua con una capacidad de 60 l/día - Simbaña Gallardo, Ángel Isaac (2018)
This project is about designing a direct expansion solar assisted heat pump. It consists of a bare flat plate collector-evaporator built in aluminum, with an emissivity of 0,03. Also, a variable speed compressor with a maximum speed of 3 600 rpm was installed. Condenser is built in a copper pipe with a thickness of 0,716 mm, in 1/4'’ y 3/16’’ diameters. Results obtained were tabulated with experimental data taken every 5 minutes in four different tests with a duration of 45 minutes for each heating process. The top temperature reached by water in the storage tank was 47,6 °C in a period of 90 minutes. The heat pump was tested in different climatic conditions. On clear days, with an average radiation value of , at an ambient temperature of 22,8 °C, it was possible to obtain water at 4,19188 °C. Similarly, in a rainy day and completely cloudy weather, with an average radiation of and 16,4 °C of ambient temperature, the maximum water temperature was 34,8899 °C. Implementing a solar system involves a high initial cost, it can be recovered, although in a long term. However, a solar system, thermal or photovoltaic, has an extend useful life, but above all, these systems contribute with the environment, due they don’t use fossil fuels or electrical energy. Implementing this heat pump can stop CO2 emissions per year. Finally, a meteorological station was used to get climatic parameters, such as ambient temperature, wind speed and incident radiation.